1991
DOI: 10.1007/bf01649428
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone concentrations in men with angiographically assessed coronary artery disease — Relationship to obesity and body fat distribution

Abstract: The relationship between circulating sex hormone levels and the occurrence of coronary artery disease (CAD) was studied in a group of 274 men undergoing coronary angiography. Hormone levels in men with CAD (n = 200) were compared to those in men found to be free of coronary lesions (n = 74). No significant differences were found for serum concentrations of estradiol, total testosterone, sex-hormone-binding globulin, free androgen index, dehydroepiandrosterone sulfate, or cortisol between the two groups. Serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Of 33 cross-sectional studies, 21 reported lower concentrations of T, BT, and/or DHEA(-S) in patients with CHD than in healthy men (14, 66, 69 -76, 79 -86, 93, 96, 98). In 12 other studies (11,44,67,68,77,78,(87)(88)(89)(90)(91)(92), similar levels of these sex hormones were found in controls and patients with CHD, and one study (68) showed elevated levels of DHEA(-S) in patients. One study (97) reported hyperestrogenemia to be related to thrombotic occlusion of the coronary arteries in MI; the mean serum estradiol level in the men who had had an MI (38.5 Ϯ 8.8 pg/ml) was higher (P ϭ 0.002) than the level in men who had not had an MI (31.9 Ϯ 7.1 pg/ml).…”
Section: Coronary Heart Disease [Angina Pectoris Myocardial Infarctisupporting
confidence: 70%
“…Of 33 cross-sectional studies, 21 reported lower concentrations of T, BT, and/or DHEA(-S) in patients with CHD than in healthy men (14, 66, 69 -76, 79 -86, 93, 96, 98). In 12 other studies (11,44,67,68,77,78,(87)(88)(89)(90)(91)(92), similar levels of these sex hormones were found in controls and patients with CHD, and one study (68) showed elevated levels of DHEA(-S) in patients. One study (97) reported hyperestrogenemia to be related to thrombotic occlusion of the coronary arteries in MI; the mean serum estradiol level in the men who had had an MI (38.5 Ϯ 8.8 pg/ml) was higher (P ϭ 0.002) than the level in men who had not had an MI (31.9 Ϯ 7.1 pg/ml).…”
Section: Coronary Heart Disease [Angina Pectoris Myocardial Infarctisupporting
confidence: 70%
“…Yang found that 2D:4D ratios, measures of masculine characteristics, and salivary testosterone showed no significant associations with one another in both male and female 18. Hauner detected no relationship between sex hormone concentrations and coronary artery disease assessed by angiography in men 38.…”
Section: Discussionmentioning
confidence: 96%
“…In both men and women, elevated DHEA-S levels were associated with retarded progression of atherosclerosis measured by coronary artery angiography (113), ultrasound carotid wall thickness (117) and pulse wave velocity aorta calcification (114). On the other hand, other groups did not confirm these findings using coronary angiography in two male samples (119,120). Retrospective studies have examined whether myocardial infarction survivors were characterized by reduced DHEA-S levels compared with healthy controls (115,116,118).…”
Section: Cardiovascular Diseasementioning
confidence: 99%